Applications of Process Engineering Principles in Materials Processing, Energy and Environmental Technologies : An EPD Symposium in Honor of Professor Ramana G. Reddy - Wang, Shijie; Free, Michael L.; Alam, Shafiq; Zhang, Mingming; Taylor, Patrick R. (The Minerals, Metals & Materials Series, 2017)
This collection offers new research findings, innovations, and industrial technological developments in extractive metallurgy, energy and environment, and materials processing. Technical topics included in the book are thermodynamics and kinetics of metallurgical reactions, electrochemical processing of materials, plasma processing of materials, composite materials, ionic liquids, thermal energy storage, energy efficient and environmental cleaner technologies and process modeling. These topics are of interest not only to traditional base ferrous and non-ferrous metal industrial processes but also to new and upcoming technologies, and they play important roles in industrial growth and economy worldwide.